Fibrocartilaginous embolism: an under-recognised cause of young spinal stroke. Issue 4 (2nd May 2022) - Nagaratnam, Sai Adithya; Lee, Raymond Lam Kwong; Sturm, Jonathan
Abstract : Fibrocartilaginous embolism is a rarely reported cause of spinal cord infarction. Seemingly innocuous activities may be associated with nucleus pulposus material embolising to the spinal cord vasculature. We describe a 36-year-old woman presenting with bilateral arm paraesthesia and chest pain that evolved into an acute cord syndrome. Initial MR scan of spine showed central spinal cord T2-weighted hyperintensity over several vertebral levels, suggesting transverse myelitis. Repeat MR scan after her symptoms persisted showed an acute cord infarction from a presumed fibrocartilaginous embolus. Clinicians should consider fibrocartilaginous embolism in patients presenting with an acute cord syndrome with supportive radiological findings.